KLASIFIKASI PNEUMONIA MENGGUNAKAN METODE SUPPORT VECTOR MACHINE - Wati, Risha Ambar; Irsyad, Hafiz; Al Rivan, Muhammad Ezar (Program Studi Teknik Informatika Universitas Multi Data Palembang, 2020)
Pneumonia is a type of lung disease caused by bacteria, viruses, fungi, or parasites. One way to find out pneumonia is by x-ray. X-rays will be analyzed to determine whether there is pneumonia or not. This study aims to classify the x-ray results whether there is pneumonia or not on the x-ray results. The classification method used in this study were Support Vector Machine (SVM) and Gray Level Co-Occurrence (GLCM) for the extraction method. There are several stages before classification, namely cropping, resizing, contrast stretching, and thresholding then extracted using GLCM and classified using SVM. The results showed that the best accuracy of 62.66%.